Time-variant reliability of timber beams according to Eurocodes considering long-term deflections. Issue 5 (2nd September 2020) - Honfi, Dániel
ABSTRACT: In order to achieve a consistent level of failure probability, structural design codes are optimized using probabilistic methods. This optimization process traditionally focuses on the ultimate limit states (ULS). However, in the design of timber structures the performance of the structural members is often governed by the serviceability limit state (SLS) associated with different load levels than applied in the ULS. The probability of serviceability failure is strongly dependent on the loading sequence and the time-dependent response of timber; therefore, a time-variant probabilistic model is recommended to estimate them properly. This study aims to investigate the time-dependent reliability for long-term deflections of timber office and residential floor beams according to the specifications of the Eurocodes. A simple creep model is used to calculate the deflections and Monte Carlo simulation is carried out to determine the reliability index. It was found that the creep factor and the suggested deflection limits given in Eurocode 5 might not be appropriate to achieve the expected target reliabilities. To obtain a more consistent reliability, more suitable values for the mentioned parameters were suggested. However, the primary aim was to present a framework to determine appropriate deflection limits for structural codes.